1986
DOI: 10.1215/03616878-11-3-393
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal to Regulate the Manner of Tobacco Advertising

Abstract: If the U.S. is to achieve the goal of reducing the initiation of smoking among adolescents, it must implement a system of tobacco advertising regulation as one component of a comprehensive prevention program. This paper proposes a system of advertising regulation which is grounded in the relevant legal, information processing, and media effects theories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Furthermore, advertising budgets are often based on a fixed percent of sales or determined by the brand's market share. Thus, these data are often hindered by a lack of both experimental control and systematic variation for the key variables such that the resulting analysis may produce ambiguous results with uncertain implications (Arbogast, 1986;Chapman, 1989;Franke, 1994;Pollay et al, 1996). The majority of the previous studies on cigarette advertising effects were not experimental in nature, which is considered to be the "gold standard" for assessing the relationship between variables (Cook & Campbell, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, advertising budgets are often based on a fixed percent of sales or determined by the brand's market share. Thus, these data are often hindered by a lack of both experimental control and systematic variation for the key variables such that the resulting analysis may produce ambiguous results with uncertain implications (Arbogast, 1986;Chapman, 1989;Franke, 1994;Pollay et al, 1996). The majority of the previous studies on cigarette advertising effects were not experimental in nature, which is considered to be the "gold standard" for assessing the relationship between variables (Cook & Campbell, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In econometric studies, regression models typically are employed; they use total industry sales as the dependent variable and total advertising expenditures of the industry as one of the predictor variables. Arbogast (11) observed that results from these studies follow the same pattern, i.e. small to moderate effects of increases in advertising expenditures on per capita consumption of cigarettes.…”
mentioning
confidence: 70%
“…These econometric studies, however, are plagued by research design problems, e.g., modeling of lagged effects of advertising expenditures; use of aggregate consumption levels primarily reflecting changes in adults, rather than changes in the level of teenage consumption; and i n a p propriate use of total industry advertising. Further, econometric studies have been unable to control for consumers' exposure to major tobacco-related events: (1) the Surgeon General's Report on Smoking and Health, (2) the ban on electronic advertising, (3) school-based health education programs, and (4) interpersonal conversations generated by these events (11).…”
mentioning
confidence: 99%
“…Most econometric research has various measurement and estimation problems, and these tend to increase the likelihood of finding ambiguous results (Arbogast, 1986;Chapman, 1989;Franke, 1994). Econometric research characteristically looks at total cigarette sales for a time period and attempts to statistically relate these sales to total advertising expenditures for that and previous time periods.…”
Section: Econometric Analysis O J Aggregnte Data Proves Littlementioning
confidence: 99%